The Lean Government Concept and Design over Copy of Administrative Document on Building Tax - Hadriyanto Hadriyanto; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2019)
Many countries have successfully to applied the Lean Government concept in administration sector especially over Indonesian government sector. The developing of government public sector is a right choices to improve service quality to the public. Thus, in this study aims to design Lean Government with DMAIC method and Lean Consumption Map tools (LCM), respectively. This method was used to increase positive impact over performance administrative copy document on building tax especially in the Badan Pendapatan Daerah (Bapenda) South Tangerang City. The result showed, a comparison between administrative document over Bapenda, South Tangerang City is different during quantitative observation from external and internal correspondence. To improve the service process over administrative copy document, we use DMAIC and Lean Consumption Map application. The significantly improvement has been obtained by the time over administrative copy document process in the Bapenda, South Tangerang City